Unintended consequences of business digitalization among MSMEs during the COVID-19 pandemic: The case of the Philippines - Keita Oikawa; Fusanori Iwasaki; Yasuyuki Sawada; Shigehiro Shinozaki (Asian Development Bank (ADB), 2025)
The coronavirus disease (COVID-19) pandemic profoundly impacted people's lives, social activities, and businesses. It particularly affected micro, small, and medium-sized enterprises (MSMEs), which account for the vast majority of firms and most of the labor force. Compared to larger firms, MSMEs were less able to absorb the pandemic's shocks, both in developed and developing economies. While digital technologies, such as e-commerce platforms, were often seen as effective tools for businesses where in-person communications are restricted, they did not guarantee the success of MSMEs. An Indonesian study showed that adopting digital technologies did not always result in positive business outcomes for MSMEs during the early stages of the pandemic (Oikawa et al. 2024a). This paper investigates whether e-commerce use in the Philippines strengthened MSME performance during the pandemic, based on a unique Asian Development Bank dataset on the impact of COVID-19 on Philippine businesses from 2020 to 2021. The findings reveal that internet or e-commerce use did not lead to better MSME outcomes during the strict lockdown in March 2020. In fact, performance sometimes worsened. However, by August 2020, the negative effects had lessened, and by March 2021, one year into the pandemic, a positive impact had emerged. These results are consistent with the Indonesia study by Oikawa et al (2024a).
Keywords: D22; G20; L20; L50; 330; digitalization; digital financial services; access to finance; SME development; SME policy; Philippines